How to provide access to next generation networks? The effect of risk allocation on investment and cooperation incentives - Christian M. Bender (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper analyzes the incentives to invest in Next Generation Access Networks (NGA) in a framework with horizontal product differentiation with price competition between an investing and an access seeking firm. Given uncertainty about the success of the NGA, I compare regulatory regimes with symmetric and with asymmetric risk allocation to the firms having the opportunity to cooperate and jointly roll-out the NGA. I find that private incentives to cooperate might coincide with the consumer surplus maximizing outcome. Whether the firms realize this socially desirable outcome depends on the outside option, i.e. the implemented access regime. The optimal regulatory policy is not only subject to the probability that the NGA succeed but depends even more on the degree of product differentiation in the retail market. Therefore, the implementation of different access regimes subject to the degree of product differentiation seems favorable. For heterogeneous retail products, an asymmetric risk allocation not only increases the chances of cooperation but lowers the risk of overinvestment. For homogeneous goods, a symmetric risk allocation is superior as it ensures sufficient investment incentives even if competition is very intensive.
Keywords: D43; K23; L13; L51; L96; 330; Next Generation Access Networks; investment; access regulation; cooperation; Breitbandkommunikation; Lichtleiterkommunikation; Investitionsrisiko; Netzzugang; Kooperation; Produktdifferenzierung; Preiswettbewerb; Lieferanten-Kunden-Beziehung; Theorie